PERILAKU KONSUMSI GIZI SEIMBANG DAN STATUS GIZI PADA REMAJA PUTRI DI SMAN 1 TARUTUNG TAHUN 2012 - Putri Natalia; Ernawati Nasution; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
The consumption of balance nutrition is a balance of nutrition that required by body, either qualitatively or quantitatively that consumed by a girl in each served food. In order to have a qualified human resource by increase the nutritional status of the people include the young girl that manifested by the daily food activities.This research is a descriptive study with cross sectional design in order to know the behavior of a teenanger in consuming the balance nutritional and nutrition status at SMAN 1 Tarutung in 2012. The behavior of balance nutrition consumption can be indicated based on knowledge, attitude and consumption pattern. The measurement is conducted by scoring method to the questionnaire with the weight that categorized in good, medium or poor, while the nutritional status can be indicated by IMT. The number of sample is 90 persons and the data is processed manually and put into a frequency distribution table and be analyzed by descriptive method.Based on the results of study, it is concluded that the knowledge and attitude of respondent to the balance nutrition is classified into 61.1% and 51.1%. While consumption pattern of respondent on the balance nutrition is classified into did not eat various food (62%) that prefer rice (100%), fish (78.9%), spinach (46.7%) and orange fruit (41.1%). And the nutritional status of respondent is classified normal (75.6%), thin (12.2%) and obese (10%) and very obese (2.2%).It is suggested to the principal and teacher at SMAN 1 Tarutung to optimize the health promotion by provide the socialization to the students when provide the lesson to maintain the nutrition sufficient to increase the learning achievement. Keywords : Behavior of teenanger, balance nutrition, nutritional status